Final Report on the Hawaiʻi P-3 Evaluation - Zellman, Gail L. (RAND Corporation, 2015)
In 2007 Hawaiʻi's P-20 Partnerships for Education launched the P-3 initiative, which aimed to have every child reading at grade level by third grade. RAND's five-year evaluation examined implementation of statewide and five community plans in six P-3 focus areas and analyzed third-grade reading scores on state reading test. More years of P-3 exposure raised reading scores modestly but significantly and increased likelihood of scoring proficient.